The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1108/s1746-979120160000012015
|View full text |Cite
|
Sign up to set email alerts
|

How Perceptions and Emotions Shaped Employee Silence in the Case of “Dr. Death” at Bundaberg Hospital

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…Inquiries into the Bristol Royal Infirmary Pediatric Scandal, the serial killer Dr. Harold Shipman, and the Mid-Staffordshire NHS Foundation Trust have all confirmed that whistleblowers played a crucial and constructive part in the identification of poor patient care that led to death and patient harm. The inquiry in the case of Dr. Jayant Patel, a surgeon at Bundaberg Hospital, Australia (Edwards et al, 2016), provides us with specific insight on how employees responded to failings in patient care over time. The role of whistleblowing here was crucial, but an analysis of the events that led to the inquiry shows, at the level of informal communication, employees were unofficially discussing their concerns during the period of sensemaking, which led to either silence or formal reporting or whistleblowing (Edwards et al, 2016).…”
Section: Why Is Understanding Employee Silence Important In Health Care?mentioning
confidence: 99%
See 1 more Smart Citation
“…Inquiries into the Bristol Royal Infirmary Pediatric Scandal, the serial killer Dr. Harold Shipman, and the Mid-Staffordshire NHS Foundation Trust have all confirmed that whistleblowers played a crucial and constructive part in the identification of poor patient care that led to death and patient harm. The inquiry in the case of Dr. Jayant Patel, a surgeon at Bundaberg Hospital, Australia (Edwards et al, 2016), provides us with specific insight on how employees responded to failings in patient care over time. The role of whistleblowing here was crucial, but an analysis of the events that led to the inquiry shows, at the level of informal communication, employees were unofficially discussing their concerns during the period of sensemaking, which led to either silence or formal reporting or whistleblowing (Edwards et al, 2016).…”
Section: Why Is Understanding Employee Silence Important In Health Care?mentioning
confidence: 99%
“…The inquiry in the case of Dr. Jayant Patel, a surgeon at Bundaberg Hospital, Australia (Edwards et al, 2016), provides us with specific insight on how employees responded to failings in patient care over time. The role of whistleblowing here was crucial, but an analysis of the events that led to the inquiry shows, at the level of informal communication, employees were unofficially discussing their concerns during the period of sensemaking, which led to either silence or formal reporting or whistleblowing (Edwards et al, 2016). When adverse events started occurring, employees engaged in discussions regarding Dr. Patel’s behaviors, performance, and decisions among themselves.…”
Section: Why Is Understanding Employee Silence Important In Health Care?mentioning
confidence: 99%
“…The inquiry in the case of Dr. Jayant Patel at Bundaberg Hospital, Australia [ 32 ] can also provide insight into how employees responded to failings in patient care over time. Once again, the role of whistleblowing here was crucial.…”
Section: Adverse Events (Aes) and Informal Communicationmentioning
confidence: 99%
“…For example, in the paper of Edwards et al a step-by-step analysis of the case of “Dr. Death” at the Bundaberg Hospital in Australia revealed that numerous allegations of harassment and bullying were filed prior to the official inquiry starting ( 49 ). The inquiry concluded that 13 patients died due to negligence, and highlighted how harassment and bullying behaviors were used to intimidate junior staff into silence.…”
Section: How Is Silence Maintained Post Residency?mentioning
confidence: 99%